Hedonic test of agarwood tea from Gyrinops versteegii with different leaves processing method - Wangiyana, I Gde Adi Suryawan; Triandini, I Gusti Agung Ayu Hari; Anita Nugraheni, Yosephin Martha Maria (Jurnal Riset Industri Hasil Hutan, 2021)
Gyrinops Agarwood tea was a potential forest tea product. This research aim is to observe panelist preference level of Gyrinops agarwood tea with different leaves processing methods. There werefour agarwood leave processing including: fresh leaves without drying and oxidation (sample1), dried leaves without oxidation (sample2), dried leaves with partial oxidation (sample3), dried leaves with full oxidation (sample4). Phytochemical screening on samples was carried by tannin measurement with titrimetric method. Five scales hedonic score and numeric score were used by the panelist to express their preference level toward the samples, including like extremely (5), like slightly (4), neither like nor dislike (3), dislike slightly (2), dislike extremely (1).Hedonic assay has shown that at least 70% of panelists are given preference scores above the rejected standard (neither like nor dislike). The panelist gave this preference based on four parameters, including color, aroma, taste, and texture. Panelists prefer samples with oxidation then sample without oxidation. This preference was related to the higher tannin concentration on the sample with oxidation than the sample without oxidation. Sample 4 has got the highest numeric score from the panelist. This sample also has the highest tannin concentration among all samples (11%). It could be concluded that dried and full oxidation on leaf processing could produce agarwood tea with high tannin concentration and hedonic scores.